Isolation of alkaliphilic microbes producing highly alkaline thermostable protease - Choo, Kin Yan (2015)
For many decades, alkaliphilic bacteria that can produce highly alkaline thermostable protease had been the focus of the intense research since they were able to perform well under high temperature and pH during many industrial processes. Proteolytic bacteria that were isolated from Selayang and Kuala Kubu Bharu hot springs in Malaysia were screened using skim milk agar plates. Isolates which showed better proteolytic activity were chosen for further identification. Bacillus licheniformis strain 1 and Bacillus licheniformis strain H were identified by using gram staining, biochemical tests and 16S rDNA sequence analysis. Protease produced by Bacillus licheniformis strain 1 reached optimum proteolytic activity at 65°C, pH 9. Its stability showed broad temperature ranges between 40 to 65°C, whereas it was stable from pH 4 to 6 for pH ranges. On the other hand, the maximum proteolytic activity showed by Bacillus licheniformis strain H was at 65°C, pH 9. Protease produced by this strain also had the potential to be stable over wide ranges of temperature and pH, that were between 40 to 60°C and from pH 4 to 11.